AB0291D PREDICTORS OF NEW BONE EROSION IN RHEUMATOID ARTHRITIS PATIENTS RECEIVING CSDMARDS: ANALYSIS OF DATA FROM THE DRIVE AND DESIRABLE STUDIES. (June 2019) - Takeuchi, Tsutomu; Soen, Satoshi; Ishiguro, Naoki; Yamanaka, Hisashi; Tanaka, Sakae; Kobayashi, Makiko; Okubo, Naoki; Nitta, Takaya; Tanaka, Yoshiya
Abstract : Background: Suppression of joint destruction is an important target for the treatment of rheumatoid arthritis (RA). Most previous studies have proposed prediction models for joint destruction to detect the risk of rapid radiographic progression (change in mTSS ≥5). As joint destruction progresses irreversibly, even slight progression of joint destruction might impact the prognosis. Therefore, our study focused on the onset of new bone erosion in RA patients. Objectives: To clarify predictors for new bone erosion in RA patients treated with csDMARDs. Methods: Predictive factors were analyzed using data from the placebo groups of the DRIVE [1] and DESIRABLE [2] studies, which were 12-month, randomized, double-blind, phase 2 and 3 trials for evaluating the efficacy of denosumab in RA patients. New bone erosion was defined as change from baseline in erosion score (ES) ≥1.0 at 12 months, which was assessed as "progressed" by two readers. In addition to newly emerging erosion, new bone erosion also included enlargement of erosion size which is the result of new erosion at a site adjacent to an existing bone erosion. To evaluate predictors for new bone erosion, a logistic regression model was applied. Significant predictors (p value of <0.1) were selected from the univariate analysis and one variable from each correlated pair that showed significance was removed. Multivariate analyses were performed using the selected predictors. Results: In a total of 306 patients, baseline DAS28-CRP (mean±SD) was 3.58±1.03. New bone erosion was observed in 90 patients (29.4%). In the univariate analysis, female sex, anti-CCP antibody positivity, rheumatoid factor (RF) positivity, tender joint count (TJC)≥6, CRP≥0.3 mg/dL, erythrocyte sedimentation rate (ESR) ≥28 mm/h, and baseline ES≥3 were identified as significant predictors for new bone erosion. RF and ESR were not included in the multivariate analysis because they were strongly correlated with anti-CCP antibody and CRP, respectively. In the multivariate analyses, female sex, anti-CCP antibody positivity, TJC≥6, CRP≥0.3 mg/dL, and baseline ES≥3 were identified as predictors for the development of new bone erosion. Conclusion: In RA patients whose disease activity was controlled on csDMARDs, positive anti-CCP antibody/RF status, elevated CRP/ESR levels, baseline ES≥3, TJC≥6 and female sex were identified as predictors for new bone erosion. References: [1] Takeuchi T, et al. Ann Rheum Dis2016;75:983–90 [2] NCT01973569 (Takeuchi T, et al: in submission) Disclosure of Interests: Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Satoshi Soen Grant/research support from: Chugai Pharmaceutical Co, . Ltd., Diaichi Sankyo Co., Ltd., Speakers bureau: Asahi Kasei Pharma Corp, Astellas Pharma Inc, Chugai Pharmaceutical Co, . Ltd., Daiichi Sankyo Co., Ltd., Eli Lilly Japan K.K., Eisai Co., Ltd. Ono Pharmaceutical CO., Ltd., Takeda Pharmaceutical Co., Ltd., Pfizer., Naoki Ishiguro Grant/research support from: AbbVie, Asahi Kasei, Astellas, Chugai, Daiichi-Sankyo, Eisai, Kaken, Mitsubishi Tanabe, Otsuka, Pfizer, Takeda, and Zimmer Biomet, Consultant for: Ono, Speakers bureau: Astellas, Bristol-Myers Squibb, Daiichi-Sankyo, Eli Lilly, Pfizer, and Taisho Toyama, Hisashi Yamanaka Grant/research support from: AbbVie, Eisai, Bristol-Meyers, Novartis, Behringer, Astellas, Kaken, Nippon-Shinyaku, Pfizer, UCB, Ayumi, Ono, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, YLbio, Speakers bureau: Bristol-Meyers, Astellas, Pfizer, Daiichi-Sankyo, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, YLbio, Sakae Tanaka Grant/research support from: KYOCERA Corporation and Asahi Kasei Corporation, Consultant for: Amgen Astellas BioPharma K.K., KYOCERA Corporation, Pfizer and Daiichi Sankyo Co., Ltd., Speakers bureau: Asahi Kasei Corporation, Astellas Pharma Inc, Ayumi Pharmaceutical Corporation, Eisai Co., Ltd., Ono Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd, Taisho Toyama Pharmaceutical Co., Ltd., Mitsubishi Tanabe pharma Corporation, Chugai Pharmaceutical Co., Ltd., Teijin Pharma Ltd., Eli Lilly, Hisamitsu Pharmaceutical Co, Inc., Pfizer, Bristol-Myers., Makiko Kobayashi Employee of: Daiichi Sankyo Co., Ltd., Naoki Okubo Employee of: Daiichi Sankyo Co., Ltd., Takaya Nitta Employee of: Daiichi Sankyo Co., Ltd., Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics